The influence of Malaysian insurance agents' career planning on their career strategies - Tan, Fee Yean; Yahya, Khulida Kirana (2013)
The aim of this study is to examine the relationship between career planning and career strategies.Based on the career planning model, this study proposes that career planning triggers the implementation of career strategies. Data were gathered through questionnaires from a sample of insurance agents (n = 531) who worked in life and general insurance companies located in the Northern states of Peninsular Malaysia.Regression analysis was performed to test the hypothesis.Results indicated that career planning is positively related to career strategy. This finding generally supports past findings, which suggest that extensive involvement in career planning activities will trigger individuals to implement career strategies to attain their career goals. The findings are discussed and implications are also provided.